The diversity of romantic pathways during emerging adulthood and their developmental antecedents. (March 2018) - Shulman, Shmuel; Seiffge-Krenke, Inge; Scharf, Miri; Boiangiu, Shira Bezalel; Tregubenko, Valerya
The present study examined patterns of romantic pathways in 100 Israeli emerging adults (54 males) who were followed from age 22 to 29 years. Analyses of interviews at age 29 yielded four distinctive romantic pathways differing in stability and ability to learn from romantic experiences: Sporadic, Lengthy Relationships but Absence of Experiential Learning, Moving from Casual to Steady Involvements, and Steady Relationships . Low efficacy, immature dependency, and level of maternal support measured 7 years earlier, predicted less optimal romantic pathways; Sporadic, and Lengthy relationships but absence of experiential learning. Distinctive gender pathways suggested that men are more likely to embark on a sporadic romantic pathway, while women tend more to prefer a stable romantic pathway. Findings of the study suggest that gender, intrapersonal capabilities, and maternal support can predict the pattern of the romantic pathway on which young people embark during their twenties.